ANALISIS KINERJA PEMERINTAH DAERAH DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN KOLAKA TIMUR - Irwan Wijayansyah; Muhammad Syarif; Muhammad Yani Balaka (JPEP (Jurnal Progres Ekonomi Pembangunan), 2022)
This study aims to analyze the impact of the performance of the Regional Government of East Kolaka Regency on improving people's welfare. This type of data uses secondary data sourced from the Regional Secretariat of East Kolaka Regency, the Regional Financial and Revenue Management Agency (BPKPD) of East Kolaka Regency, and the Central Statistics Agency (BPS) of East Kolaka Regency. The data analysis used in this research is a quanitative descriptive.The results of this study indicate that the impact of the performance of the Regional Government of East Kolaka Regency is said to be less good in order to improve the welfare of the community, especially when they are in the midst of the Covid-19 pandemic. This can be seen from the achievement of the performance indicators of the Regional Government of East Kolaka Regency which are listed in the Performance Accountability Report of Government Agencies (LAKIP) showing indicators of community welfare, namely the percentage of the Human Development Index (HDI) which decreased in 2020 compared to the percentage of HDI in 2019, where the decline in HDI was followed by an increase in the number of poor people in 2020.Keywords: Local Government Performance, Community Welfare, LAKIP, IPM